2000
DOI: 10.1093/jexbot/51.349.1423
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of globulin mobilization and cysteine proteinases in embryonic axes and cotyledons during germination and seedling growth of vetch (Vicia sativa L.)

Abstract: Vicilin and legumin, the storage globulins of mature dry vetch (Vicia sativa L.) seeds, are found in protein bodies which are present not only in the cotyledons, but also in the radicle, axis and shoot (together, for reasons of simplicity, here called axis). When at 24 h after the start of imbibition (hai) the radicle breaks through the seed coat a major part of the globulins in the axis has already been degraded, whereas in the cotyledons globulin breakdown cannot yet be detected. Globulin mobilization starts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 34 publications
5
68
0
Order By: Relevance
“…Total proteins were extracted with 100 mM tris-HCL buffer (pH 8.0) containing 150 mM NaCl and 1 µ mL -1 a-mercapto-ethanol. Proteins were extracted in the dark for 15 min, centrifuged at 15,000 g at 4 °C for 20 min (Schlereth et al 2000). The supernatant was stored for subsequent analysis.…”
Section: Protein Assaymentioning
confidence: 99%
“…Total proteins were extracted with 100 mM tris-HCL buffer (pH 8.0) containing 150 mM NaCl and 1 µ mL -1 a-mercapto-ethanol. Proteins were extracted in the dark for 15 min, centrifuged at 15,000 g at 4 °C for 20 min (Schlereth et al 2000). The supernatant was stored for subsequent analysis.…”
Section: Protein Assaymentioning
confidence: 99%
“…It was the first proteinase ever known which in vitro extensively degraded native phaseolin, the major storage globulin of this grain legume (Senyuk et al, 1998). In vetch (Vicia sativa) seeds, the legumain-like VsPB2 and proteinase B together with additional papain-like cysteine proteinases were responsible for the bulk breakdown and mobilization of storage globulins during seed germination (Schlereth et al, 2000). In Arabidopsis, the seed protein profiles were compared between the wild type and a seed-type vacuolar processing enzyme VPE mutant using a two dimensional gel/mass spectrometric analysis.…”
Section: Association Of Vacuolar Processing Enzyme and Papain-like Cymentioning
confidence: 99%
“…Papain-like cysteine protease such as CPR2 and CPR4 are found in cotyledon and axis of dry and imbibed seeds. Gene expression studies concluded that storage globulin mobilization in germinating vetch seeds is started by the stored cysteine proteases (CPRs), however, the bulk globulin mobilization is mediated by de novo synthesized CPRs (Schlereth et al, 2000;Schlereth et al, 2001;Tiedemann et al, 2001). These data suggest that papain-like cysteine proteases may play physiological roles and functions in association with seed storage globulin protein degradation and mobilization during seed germination and seedling growth.…”
Section: Association Of Vacuolar Processing Enzyme and Papain-like Cymentioning
confidence: 99%
See 2 more Smart Citations